2021
DOI: 10.1002/aic.17416
|View full text |Cite
|
Sign up to set email alerts
|

Combining trace Pt with surface silylation to boost Au/uncalcined TS‐1 catalyzed propylene epoxidation with H2 and O2

Abstract: Modification of bifunctional Au‐Ti catalysts for direct epoxidation of propylene with H2 and O2 is of burgeoning interest for potential commercialization requirements with desirable overall catalytic performance. Herein, we report a strategy by combining the addition of trace Pt into Au particles to enhance hydroperoxide species formation with the surface silylation to promote propylene oxide (PO) desorption. The resultant catalyst, that is, silylated Au20Pt1/uncalcined TS‐1, gives rise to significantly enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…For the AuNPs, five diffraction peaks are presented at 2 θ values of 38.3°, 44.5°, 64.7°, 77.6°, and 81.8°, corresponding to the (111), (200), (220), (311), and (222) planes of fcc Au (JCPDS card #04-0784), respectively. 29 With the incorporation of SiO 2 particles, a broad peak appeared at 2 θ ranging from 20° to 30°, which is likely due to the amorphous nature of silica. The elemental composition and distribution of the Au-based nanoparticles were studied by depositing particles on aluminium plates, and examined by SEM–EDX analysis.…”
Section: Resultsmentioning
confidence: 95%
“…For the AuNPs, five diffraction peaks are presented at 2 θ values of 38.3°, 44.5°, 64.7°, 77.6°, and 81.8°, corresponding to the (111), (200), (220), (311), and (222) planes of fcc Au (JCPDS card #04-0784), respectively. 29 With the incorporation of SiO 2 particles, a broad peak appeared at 2 θ ranging from 20° to 30°, which is likely due to the amorphous nature of silica. The elemental composition and distribution of the Au-based nanoparticles were studied by depositing particles on aluminium plates, and examined by SEM–EDX analysis.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, the absence of Au 3+ species indicates that Au 3+ is completely reduced after the pretreatment. The Ti 2p spectra in Figure b have been deconvoluted into Ti 4+ and Ti 3+ peaks according to the literature. ,, As can be seen in Figure b, as the crystal size increases, the binding energy of Ti 2p shifts to the low energy region, while the Au 4f binding energy shifts to the high energy region. It can be speculated that electrons have been transferred between Au and Ti.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the surface Ti atoms of TS-1-CTES and HTS-1 show a higher binding energy than that of TS-1, which is attributed to their electron-deficient property. 5,35,36 The electronic environment around the Ti atoms of TS-1-CTES and HTS-1 is distinct, maybe due to the confinement of the pore structure. It is advantageous to the adsorption of *OOH species and C 3 H 6 through the attraction interaction between the empty orbit of the framework Ti atoms and their charges.…”
Section: ■ Results and Discussionmentioning
confidence: 99%